Fatigue Damage Analysis Of Automobile Steering Knuckle Using Finite Element Analysis - Kamarul Ariffin, Zakaria; Ad Suhadak, Fadrah Hanim; Mohd Razalli, Ammer Ezhar; Kassim, M.S (Asian Research Publishing Network (ARPN), 2017)
-